Study of Antennas in C Band for Satellite Communication - Rohilla, Hiteshwer; Batra, Monish; Kumar, Krishan (Journal of Advance Research in Electrical & Electronics Engineering (ISSN 2208-2395), 2014)
The main focus of this paper on the various types of antenna used in C band for satellite communication. This paper gives information to reader about the antennas used for C band. It gives overview about the patch antenna and dish antenna and their individual losses and performance. In the end of paper we discuss some of antennas that can be used for future aspects in satellite communication.